Antioxidant Activity and Organoleptic Quality of Probiotic Tepache of Pineapple Peel Sugar Variation and Fermentation Duration - Abdurrahman, Fithrotul Haq Rabbani; Suryani, Titik (Universitas Muhammadiyah Surakarta, 2023)
Tepache is a probiotic beverage from fermented product beneficial to health, which can improve the balance of good bacteria and reduce the risk of gastrointestinal disease. The content of honey pineapple peel includes carbohydrates 17.53 %, protein 4.41 %, reducing sugar 13.65 % and vitamins C and E which act as antioxidant. This research was aimed to determine the antioxidant activity and organoleptic quality of probiotics tepache beverage of pineapple peel with variation of sugar and fermentation duration. This research method used experimental and Complete Random Design (CRD) with two factors. The factor I was the type of sugar is 80 g granulated sugar (G1) and 80 g palm sugar G2). Factor II was the fermentation duration in three days (F1) and five days (F2). The result showed that the highest antioxidant activity of pineapple peel tepache was 67.14 % in G2F1 (palm sugar + 3 days fermentation duration). The best organoleptic quality of pineapple peel tepache at G2F1 (palm sugar + 3 days fermentation duration) was brown color, sour taste, and slightly pineapple aroma.